Angiotensin II Type 1 Receptor Antibodies: Great Expectations?. Issue 10 (7th August 2013) - Tinckam, K.; Campbell, P.
<x xml:space="preserve">Abstract</x> Newly available commercial assays for angiotensin II type 1 receptor antibodies provide an opportunity for examining the role of non‐HLA antibodies in kidney transplantation, but data do not yet support their widespread clinical use. See articles by Giral et al (page 2567) and Taniguchi et al (page 2577).